2012
DOI: 10.1167/iovs.11-8730
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Use of Multiple Comparison Corrections in Ophthalmology Research

Abstract: PURPOSE. The probability of type I error, or a false-positive result, increases as the number of statistical comparisons in a study increases. Statisticians have developed numerous corrections to account for the multiple comparison problem. This study discusses recent guidelines involving multiple comparison corrections, calculates the prevalence of corrections in ophthalmic research, and estimates the corresponding number of false-positive results reported at a recent international research meeting.METHODS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A lack of a comprehensive examination of interactions between a large number of the independent variables in the final models may have produced some random suppression/mediating effects of some variables on other variables. Type 1 error, a false-positive result, was also likely to occur because of the large set of comparisons [57, 58]. On the basis of the exploratory nature of the study, however, concerns about type 1 error associated with multiple comparisons may not be a serious problem with the preliminary study findings [59].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of a comprehensive examination of interactions between a large number of the independent variables in the final models may have produced some random suppression/mediating effects of some variables on other variables. Type 1 error, a false-positive result, was also likely to occur because of the large set of comparisons [57, 58]. On the basis of the exploratory nature of the study, however, concerns about type 1 error associated with multiple comparisons may not be a serious problem with the preliminary study findings [59].…”
Section: Discussionmentioning
confidence: 99%
“…Since this is an exploratory study, we did not implement multi-testing corrections to identify significant association findings. Prior studies have suggested that an inflated familywise error rate (FWER) due to a lack of multi-testing corrections may be acceptable in an exploratory study, since the hypothesis would need to be addressed a priori and cannot be discerned by any a posteriori analysis (Goeman and Solari, 2014; Stacey et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The best practice to correct for these numerous statistical comparisons is by modifying the significance level (p-value) to account for the number of comparison made in the study [57]. When restricting the fMRI analysis to a brain region of interest, one accepted way to do this is using small volume correction (corresponding to the number of voxels compared) with the family wise error (FWE) rate (type I error rate) [58]. However, it is also important to consider that adopting the most conservative approach (FWE rate) may lead to increasing the rate of type II errors (false negatives) [59].…”
Section: The Role Of Kibra In Episodic Memory In Healthy Subjectsmentioning
confidence: 99%